A conductive hydrogel microneedle patch for myocardial repair and preparation method thereof

By designing a conductive hydrogel microneedle patch containing a conductive layer, an adhesive layer and a stain-resistant layer, the versatility problem that the prior art is difficult to provide simultaneously with myocardial repair, and effective mechanical support, electrical signaling and adhesion prevention effects are achieved.

CN118949084BActive Publication Date: 2025-04-01BEOGENE BIOTECH GUANGZHOU
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411341946.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-25
Publication Date
2025-04-01
Estimated Expiration
2044-09-25

AI Technical Summary

Technical Problem

The prior art is difficult to simultaneously provide the mechanical support required for myocardial repair, promote vascularization, remove reactive oxygen species, improve electrical signaling and prevent tissue adhesion.

Method used

A conductive hydrogel microneedle patch is designed, including a backing and a microneedle array. The backing consists of a stain-resistant layer, an adhesive layer and a conductive layer. The adhesive layer contains methacrylylated glycine and reduced graphene oxide. The conductive layer provides mechanical support and conductivity, and the stain-resistant layer prevents adhesion.

Benefits of technology

This patch can effectively provide mechanical support, promote electrical signal transmission between cardiomyocytes, prevent tissue adhesion, and achieve drug delivery depth in the internal environment, significantly improving the myocardial repair effect.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118949084B_ABST
    Figure CN118949084B_ABST
Patent Text Reader

Abstract

The present invention relates to a conductive hydrogel microneedle patch for myocardial repair and a preparation method thereof. The microneedle patch comprises a backing and a microneedle array, wherein the microneedle array is solidified from a hydrogel solution I and comprises methacrylylated dextran, epigallocatechin gallate, and basic fibroblast growth factor; the backing comprises an adhesion layer and an antifouling layer, wherein the adhesion layer comprises methacrylylated glycine and reduced graphene oxide; and the antifouling layer comprises polyethylene glycol diacrylate. The microneedle patch of the present invention has a needle tip loaded with a drug, a backing having a conductive adhesion layer, and an antifouling layer, which can provide mechanical support to the damaged cardiac tissue, effectively ensure the drug delivery depth, and can adhere well to the tissue surface, promote the conduction of electrical signals between myocardial cells, and avoid adhesion between the microneedle patch and other tissues and organs in the in vivo environment, and has a good cardiac repair effect and can be applied to the in vivo environment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of medical biomaterials, and in particular to a conductive hydrogel microneedle patch for myocardial repair and a preparation method thereof. Background Art

[0002] The myocardium is a tissue that contracts and relaxes in response to electrical impulses. After myocardial infarction, many changes occur in the myocardial microenvironment, including fluctuations in the abundance of reactive oxygen species (ROS) and inflammatory factors. ROS are overexpressed in the infarcted myocardium, disrupting cellular homeostasis and leading to myocardial cell damage, while promoting inflammation and myocardial fibrosis. Excessive activation of inflammation can lead to maladaptive healing and ventricular remodeling. In addition, the reduced oxygen and nutrient supply caused by coronary artery occlusion can lead to the development of fibrous scar tissue, thereby increasing the resistivity of myocardial tissue and hindering electrical signals between myocardial cells, causing abnormal synchronous contraction between normal myocardial tissue and fibrous scar tissue, and ultimately leading to ventricular dysfunction. Therefore, in order to reverse this unfavorable microenvironment, reconstructing electrical signal conduction and / or promoting angiogenesis in the infarct area can promote the repair of cardiac function. Various biomaterials have been used to promote cardiac function recovery after myocardial infarction, including nanomaterials, hydrogels, and cardiac patches.

[0003] In general, nanomaterials can achieve selective accumulation in the infarct area by targeting the site of myocardial injury and inflammation; however, strategies based on nanomaterials are limited by potential toxicity and lack of mechanical support in the treatment of myocardial infarction. In addition, although hydrogels injected into the myocardium can directly reach the infarct area and provide support for the ventricular wall, synthetic hydrogels are prone to swell due to water absorption, exerting pressure on the surrounding tissues; and injectable gels generally have a low modulus and degrade quickly in vivo, which cannot achieve long-term therapeutic effects. In recent years, the study of hydrogel myocardial patches in myocardial tissue engineering has also gained widespread attention. Some biomaterials with regulatable structural properties can be prepared into cardiac patches with good biocompatibility. These patches can provide mechanical support for cell growth and help repair damaged hearts. However, in general, single-layer hydrogel patches prepared from natural biomaterials are conducive to cell adhesion and are prone to tissue adhesion problems in vivo. Therefore, it is still a challenge to manufacture a multifunctional cardiac patch that has biomimetic mechanical properties to provide mechanical support, promote vascularization of infarcted tissue, scavenge reactive oxygen species, improve electrical signal conduction, and prevent tissue adhesion. Summary of the invention

[0004] In view of the above-mentioned deficiencies in the prior art, the present invention provides a conductive hydrogel microneedle patch for myocardial repair and a preparation method thereof.

[0005] The specific technical scheme of the present invention is as follows:

[0006] In a first aspect of the present invention, a conductive hydrogel microneedle patch for myocardial repair is provided, comprising a backing and a microneedle array, wherein the microneedle array is solidified from a hydrogel solution I, wherein the hydrogel solution I comprises methacryloylated dextran (DexMA), epigallocatechin gallate (EGCG), and basic fibroblast growth factor (bFGF); the backing comprises an adhesion layer and an anti-fouling layer, wherein the adhesion layer is connected to the microneedle array, is located on the inner side of the backing, and is solidified from a hydrogel solution II, wherein the hydrogel solution II comprises methacryloylated glycine (ACG) and reduced graphene oxide (rGO); the anti-fouling layer is located on the outer side of the backing, and is solidified from a hydrogel solution III, wherein the hydrogel solution III comprises polyethylene glycol diacrylate (PEGDA).

[0007] First, the microneedle array contains methacryloyl dextran (DexMA), epigallocatechin gallate (EGCG), and basic fibroblast growth factor (bFGF). DexMA is a polymer hydrogel with good biocompatibility. The three-dimensional network structure formed by cross-linking can provide a platform for the efficient loading and release of EGCG and bFGF. bFGF can promote angiogenesis by promoting the proliferation and migration of vascular endothelial cells and inducing the transformation of surrounding fibroblasts into vascular endothelial cells. EGCG has a variety of biological activities, including antioxidant, anti-inflammatory, anti-tumor, and anti-aging; it helps to reduce oxidative stress and inflammatory response in cells, promote myocardial repair and regeneration, and bFGF also has a certain effect on the antioxidant activity of EGCG. Secondly, in the adhesion layer, the basic network is formed by ACG, and the introduction of rGO can form a stable conductive network, which can be used as a conductive scaffold for the heart patch to promote the conduction of electrical signals between myocardial cells and contribute to the normal function of the heart. Moreover, the two-dimensional structure and high specific surface area of ​​rGO give it good mechanical support properties, which can enhance the stability and structural strength of the patch; the anti-fouling layer structure can prevent tissue adhesion and avoid adhesion.

[0008] Preferably, the hydrogel solution I comprises 1 mg / mL-10 mg / mL of epigallocatechin gallate, 100 mg / mL-300 mg / mL of methacryloyl dextran, and 0.001 mg / mL-0.01 mg / mL of basic fibroblast growth factor. In a preferred embodiment, it comprises 10 mg / mL of epigallocatechin gallate, 300 mg / mL of methacryloyl dextran, and 0.01 mg / mL of basic fibroblast growth factor.

[0009] In some embodiments, the methacryloyl dextran is prepared by the following method: mixing dextran, dimethyl sulfoxide and 4-dimethylaminopyridine, stirring, adding glycidyl methacrylate, stirring, dialyzing, and freeze-drying to obtain the methacryloyl dextran. Preferably, dextran: dimethyl sulfoxide: 4-dimethylaminopyridine: glycidyl methacrylate = 5.0 g: 50 mL: 1 g: 1.5 mL.

[0010] Preferably, the hydrogel solution II comprises, based on the amount of water, 20 wt % methacryloylated glycine and 5 mg / mL reduced graphene oxide.

[0011] In some embodiments, the reduced graphene oxide is prepared by mixing L-ascorbic acid and graphene oxide aqueous solution at pH = 9 and 90° C. Preferably, L-ascorbic acid: graphene oxide = 0.5 g: 50 mg, and the concentration of the graphene oxide aqueous solution is 1 mg / mL.

[0012] In some embodiments, the graphene oxide is prepared by adding graphite to concentrated sulfuric acid, stirring in a low-temperature ice bath, adding potassium permanganate in batches, stirring the reaction in a 37°C water bath after sufficient mixing, and then stirring the reaction at 25°C; then, slowly adding deionized water I to the reaction solution, heating the water bath to 90°C for reaction after the generated gas is released, and finally adding deionized water II to dilute the reaction solution, cooling the reaction solution to room temperature naturally after the reaction is terminated, adding 30% hydrogen peroxide solution until no bubbles are generated, and standing the reaction solution for cooling, reacting with 10% dilute hydrochloric acid and barium chloride solution, repeatedly centrifuging until no precipitation is generated, and continuing to use deionized water to wash until the reaction solution is neutral to obtain the graphene oxide. Preferably, graphite: concentrated sulfuric acid: potassium permanganate: deionized water I: deionized water II = 2g: 25mL: 7g: 120mL: 200mL.

[0013] In some embodiments, the methacryloylated glycine is prepared by the following method: dissolving sodium glycine in a NaOH solution under ice bath conditions, then dropping an acryloyl chloride-tetrahydrofuran solution into the solution, reacting, then washing and removing impurities, extracting, drying and concentrating, dissolving the obtained product in water, and freeze-drying to obtain the methacryloylated glycine. Preferably, the concentration of the NaOH solution is 6M, in the acryloyl chloride-tetrahydrofuran solution, acryloyl chloride:tetrahydrofuran = 5.5:10 (volume ratio), sodium glycine: NaOH solution: acryloyl chloride-tetrahydrofuran solution = 5g:25mL:15.5mL.

[0014] Preferably, in the hydrogel solution III, the content of polyethylene glycol diacrylate is 10% based on the amount of water.

[0015] In some embodiments, the polyethylene glycol diacrylate is prepared by the following method: dissolving polyethylene glycol in anhydrous toluene at 40°C under nitrogen, adding triethylamine after cooling to room temperature, stirring evenly, adding acryloyl chloride dropwise, stirring to react, and then precipitating the obtained polymer in n-hexane, purifying the precipitate, then dissolving it in water, dialyzing it, and freeze-drying it. Preferably, polyethylene glycol: anhydrous toluene: triethylamine: acryloyl chloride = 8g: 40mL: 1.19mL: 0.81mL.

[0016] Photoinitiator, tartrazine and the like may be further added to the hydrogel solutions I, II and III of the present invention as required.

[0017] The present invention also provides a method for preparing the conductive microneedle patch. The conductive hydrogel microneedle patch can be prepared by 3D printing and curing. The printing order is: anti-fouling layer, adhesion layer, microneedle array. After printing, the completely polymerized monomers are removed by water immersion, and the conductive microneedle patch is obtained after drying and demolding.

[0018] The beneficial effects of the present invention are:

[0019] The present invention designs a drug-loaded microneedle patch for myocardial repair, in which the needle tip is loaded with drugs, the backing has a conductive adhesion layer, and also has an anti-fouling layer. It can provide mechanical support to damaged cardiac tissue and effectively ensure the drug delivery depth, and can also adhere well to the tissue surface to promote electrical signal conduction between myocardial cells, while avoiding adhesion between the microneedle patch and other tissues and organs in the in vivo environment. The repair effect is good and can be applied to the in vivo environment. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 This is a schematic diagram of the structure of the conductive hydrogel microneedle patch for myocardial repair of the present invention;

[0021] Figure 2 This is a physical picture of the conductive hydrogel microneedle patch for myocardial repair of the present invention;

[0022] Figure 3 The antioxidant capacity analysis results of the microneedle patch of the embodiment of the present invention;

[0023] Figure 4 The figures are the evaluation results of the anti-inflammatory effect of the microneedle patch according to the embodiment of the present invention. DETAILED DESCRIPTION

[0024] The present invention provides a conductive hydrogel microneedle patch for myocardial repair, the structure of which is referenced Figure 1, including a backing and a microneedle array, the microneedle array is solidified by a hydrogel solution I, and the hydrogel solution I includes methacryloyl dextran (DexMA), epigallocatechin gallate (EGCG), and basic fibroblast growth factor (bFGF); that is, EGCG and bFGF are introduced into the DexMA hydrogel system, and bFGF can promote angiogenesis by promoting the proliferation and migration of vascular endothelial cells and inducing the transformation of surrounding fibroblasts into vascular endothelial cells. Secondly, EGCG has a variety of biological activities, including anti-oxidation, anti-inflammatory, anti-tumor, anti-aging, etc., which helps to reduce oxidative stress and inflammatory response in cells and promote myocardial repair and regeneration.

[0025] The backing includes an antifouling layer and an adhesive layer. The adhesive layer is connected to the microneedle array and is located on the inner side of the backing. It is solidified from a hydrogel solution II. The hydrogel solution II contains polyethylene glycol diacrylate (ACG) and reduced graphene oxide (rGO). rGO has excellent conductivity. By dispersing it in the ACG gel, a stable conductive network can be formed, forming a continuous conductive path, which can be used as a conductive scaffold for the patch to promote electrical signal conduction between myocardial cells and contribute to the normal function of the heart. In addition, the two-dimensional structure and high specific surface area of ​​graphene oxide give it good mechanical support properties, which can enhance the stability and structural strength of the heart patch.

[0026] The anti-fouling layer is located on the outside of the backing and is solidified by the hydrogel solution III. The hydrogel solution III includes polyethylene glycol diacrylate (PEGDA), which can prevent the microneedle patch from adhering to other tissues and organs in the in vivo environment.

[0027] The various structures of the microneedle in the embodiment of the present invention cooperate and support each other, which can not only provide mechanical support to the damaged cardiac tissue and effectively ensure the depth of drug delivery, but also adhere well to the tissue surface to promote the conduction of electrical signals between myocardial cells, while avoiding adhesion between the microneedle patch and other tissues and organs in the in vivo environment, and has a good cardiac repair effect.

[0028] In order to facilitate the understanding of the present invention, the present invention will be described more fully below with reference to the relevant drawings and embodiments. The preferred embodiments of the present invention are given below. However, the present invention can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the understanding of the disclosure of the present invention more thorough and comprehensive.

[0029] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used in the specification of the present invention herein are only for the purpose of describing specific embodiments and are not intended to limit the present invention.

[0030] Unless otherwise specified, the reagents, materials, and equipment used in the examples of the present invention are all commercially available; the test methods, unless otherwise specified, are all conventional test methods in the art.

[0031] Raw material preparation

[0032] (1) Preparation of methacryloylated dextran (DexMA)

[0033] First, weigh 5.0g of dextran, add it to 50mL of dimethyl sulfoxide (DMSO), stir it under magnetic stirring for 1h, and dissolve it into a clear light yellow uniform solution. Then add 1g of 4-dimethylaminopyridine (DMAP) to the dextran solution, continue stirring for 0.5, and dissolve it into a clear light green uniform solution; then, add 1.5mL of glycidyl methacrylate (GMA), stir in the dark for 48h; finally, transfer the reaction solution to a cellulose dialysis bag with a molecular weight cutoff of 14000Da, and dialyze it in deionized water for 3 days to remove by-products. The dialyzed reaction solution was freeze-dried for 48h to obtain methacryloyl dextran (DexMA).

[0034] (2) Preparation of graphene oxide (GO)

[0035] First, weigh 2g of graphite and add 25mL of concentrated sulfuric acid (stirred in a low-temperature ice bath). Add 7g of potassium permanganate powder in batches within 2h, stir slowly to make it fully mixed, then switch to a 37°C water bath for continuous reaction for 1h, and then stir at 25°C for 24h. Subsequently, 120mL of deionized water is slowly added to the reaction solution. At this time, the temperature of the reaction solution will rise instantly, and a large amount of gas will be generated. After that, the water bath is heated to 90°C, and the reaction is allowed to proceed for 30 minutes. Finally, 200mL of deionized water is added to dilute the reaction solution. After the reaction is terminated, it is naturally cooled to room temperature, and 30% hydrogen peroxide solution is added until no bubbles are generated. After the reaction solution is cooled, 10% dilute hydrochloric acid reacts with the barium chloride solution, and centrifuges repeatedly until no precipitation is produced. Continue to use deionized water to completely wash until the reaction solution is neutral. Finally, the reaction solution is vacuum freeze-dried for 24 hours to obtain a brown-yellow powder.

[0036] (3) Synthesis of reduced graphene oxide (rGO)

[0037] Take 0.05g of graphene oxide powder, add 50mL of deionized water, stir for 30min, ultrasonicate for 15min, and obtain 1mg / mL GO dispersion for standby use. Add 0.5g of L-ascorbic acid to 50mL of reduced graphene oxide suspension with a concentration of 1mg / mL and stir at 90°C, and adjust the pH of the dispersion to 9 with 25% ammonia solution. The reaction time is 20min, and stand at room temperature for 24h to allow the reduction reaction to proceed thoroughly, and obtain reduced graphene oxide dispersion. Wash the reaction solution with deionized water until it is neutral. Finally, the reaction solution is freeze-dried in vacuum for 48h to obtain a dark brown powder.

[0038] (4) Synthesis of polyethylene glycol diacrylate (PEG)

[0039] 8 g of polyethylene glycol (PEG) was dissolved in 40 mL of anhydrous toluene at 40 ° C under nitrogen atmosphere, and 1.19 mL of triethylamine was added after cooling to room temperature. After stirring evenly, 0.81 mL of acryloyl chloride was added dropwise, and stirred at room temperature for 2 h. The resulting polymer was precipitated in n-hexane, and the precipitate was further purified by toluene and n-hexane three times. Then, the purified polyethylene glycol diacrylate (PEGDA) was dissolved in deionized water and dialyzed (MW: 1000 Da) for 3 days, centrifuged at 10000 rpm for 10 minutes to remove impurities, and the supernatant was freeze-dried and stored at -20 ° C until use.

[0040] (5) Synthesis of methacryloylated glycine (ACG)

[0041] Dissolve 5g of sodium glycinate in 6M NaOH solution (25ml) and stir for 20min in an ice bath. Add 5.5ml of acryloyl chloride to 10ml of tetrahydrofuran, stir and slowly add dropwise to the above solution for 2h, and continue ice bathing for 1h after the addition is complete. Add 10ml of water to the resulting solution, wash three times with ether to remove impurities, adjust the pH of the aqueous phase to 2, add NaCl to saturate, and finally extract with ethyl acetate several times. After drying and concentration, the obtained product is dissolved in 10ml of water and lyophilized to obtain ACG.

[0042] Microneedle patch preparation

[0043] Table 1 Raw material composition of different embodiments and comparative examples

[0044]

[0045]

[0046] Example 1

[0047] A microneedle patch, the preparation method of which is as follows:

[0048] S1 Preparation of hydrogel solution

[0049] Hydrogel solution III: 2 g of PEGDA was dissolved in 20 mL of deionized water to obtain a 10% PEGDA solution, and 12 mg of tartrazine and 20 mg of LAP photoinitiator were added to obtain hydrogel solution III, which was used for curing to prepare an antifouling layer.

[0050] Hydrogel solution II: 100 mg of reduced graphene oxide was added to 20 mL of deionized water to obtain a reduced graphene oxide aqueous dispersion with a dispersion concentration of 5 mg / mL. The solution was ultrasonically treated for 1 h to obtain a stable and uniform reduced graphene oxide / water dispersion, and then 4 g of ACG was added to 20 mL of the reduced graphene oxide aqueous dispersion, and 12 mg of lemon yellow and 20 mg of LAP photoinitiator were added to obtain hydrogel solution II, which was used for curing to prepare an adhesion layer.

[0051] Hydrogel solution I: 1 mg of EGCG and 300 mg of DexMA were dissolved in 1 mL of deionized water to form an EGCG / DexMA solution, 0.01 mg of bFGF was added to the EGCG / DexMA solution, and then 0.6 mg of tartrazine and 1 mg of photoinitiator were added to obtain hydrogel solution I, which was used for curing to prepare a microneedle array.

[0052] S2 3D curing printing

[0053] The prepared hydrogel solution is added into the material tank in sequence. The printing order is anti-fouling layer, adhesion layer, and microneedle array. After each layer is printed, new solution is added into the material tank.

[0054] Curing conditions of the outer anti-fouling layer as the microneedle backing: light intensity 15mW / cm 2 , exposure time 15s, base layer exposure time 17s.

[0055] Curing conditions for the inner adhesive layer of the microneedle backing: light intensity 16mW / cm 2 , exposure time 16s, base layer exposure time 18s.

[0056] Curing conditions of microneedle array: light intensity 13mW / cm 2 , exposure time 16s, base layer exposure time 16s.

[0057] After printing, soak it in water for 5 minutes to remove the incompletely polymerized monomers. After drying and demoulding, a conductive microneedle patch can be obtained.

[0058] Example 2

[0059] A microneedle patch, the preparation method of which is as follows:

[0060] S1 Preparation of hydrogel solution

[0061] Hydrogel solution III: 2 g of PEGDA was dissolved in 20 mL of deionized water to obtain a 10% PEGDA solution, and 12 mg of tartrazine and 20 mg of LAP photoinitiator were added to obtain hydrogel solution III, which was used for curing to prepare an antifouling layer.

[0062] Hydrogel solution II: 100 mg of reduced graphene oxide was added to 20 mL of deionized water to obtain a reduced graphene oxide aqueous dispersion with a dispersion concentration of 5 mg / mL. The solution was ultrasonically treated for 1 h to obtain a stable and uniform reduced graphene oxide / water dispersion, and then 4 g of ACG was added to 20 mL of the reduced graphene oxide aqueous dispersion, and 12 mg of lemon yellow and 20 mg of LAP photoinitiator were added to obtain hydrogel solution II, which was used for curing to prepare an adhesion layer.

[0063] Hydrogel solution I: 10 mg of EGCG and 300 mg of DexMA were dissolved in 1 mL of deionized water to form an EGCG / DexMA solution, 0.01 mg of bFGF was added to the EGCG / DexMA solution, and then 0.06 wt% mg of tartrazine and 0.1 wt% of LAP photoinitiator were added to obtain hydrogel solution I, which was used for curing to prepare a microneedle array.

[0064] S2 3D curing printing

[0065] The prepared hydrogel solution is added into the material tank in sequence. The printing order is anti-fouling layer, adhesion layer, and microneedle array. After each layer is printed, new solution is added into the material tank.

[0066] Curing conditions of the outer anti-fouling layer as the microneedle backing: light intensity 15mW / cm 2 , exposure time 15s, base layer exposure time 17s.

[0067] Curing conditions for the inner adhesive layer of the microneedle backing: light intensity 16mW / cm 2 , exposure time 16s, base layer exposure time 18s.

[0068] Curing conditions of microneedle array: light intensity 13mW / cm 2 , exposure time 16s, base layer exposure time 16s. After printing, soak in water for 5min to remove the incompletely polymerized monomers. After drying and demoulding, a conductive microneedle patch can be obtained.

[0069] Example 3

[0070] A microneedle patch, the preparation method of which is as follows:

[0071] S1 Preparation of hydrogel solution

[0072] Hydrogel solution III: 2 g of PEGDA was dissolved in 20 mL of deionized water to obtain a 10% PEGDA solution, and 12 mg of tartrazine and 20 mg of LAP photoinitiator were added to obtain hydrogel solution III, which was used for curing to prepare an antifouling layer.

[0073] Hydrogel solution II: 100 mg of reduced graphene oxide was added to 20 mL of deionized water to obtain a reduced graphene oxide aqueous dispersion with a dispersion concentration of 5 mg / mL. The solution was ultrasonically treated for 1 h to obtain a stable and uniform reduced graphene oxide / water dispersion, and then 4 g of ACG was added to 20 mL of the reduced graphene oxide aqueous dispersion, and 12 mg of lemon yellow and 20 mg of LAP photoinitiator were added to obtain hydrogel solution II, which was used for curing to prepare an adhesion layer.

[0074] Hydrogel solution I: 1 mg of EGCG and 100 mg of DexMA were dissolved in 1 mL of deionized water to form an EGCG / DexMA solution, 0.001 mg of bFGF was added to the EGCG / DexMA solution, and then 0.06 wt% mg of tartrazine and 0.1 wt% of LAP photoinitiator were added to obtain hydrogel solution I, which was used for curing to prepare a microneedle array.

[0075] S2 3D curing printing

[0076] The prepared hydrogel solution is added into the material tank in sequence. The printing order is anti-fouling layer, adhesion layer, and microneedle array. After each layer is printed, new solution is added into the material tank.

[0077] Curing conditions of the outer anti-fouling layer as the microneedle backing: light intensity 15mW / cm 2 , exposure time 15s, base layer exposure time 17s.

[0078] Curing conditions for the inner adhesive layer of the microneedle backing: light intensity 16mW / cm 2 , exposure time 16s, base layer exposure time 18s.

[0079] Curing conditions of microneedle array: light intensity 13mW / cm 2 , exposure time 16s, base layer exposure time 16s.

[0080] After printing, soak it in water for 5 minutes to remove the incompletely polymerized monomers. After drying and demoulding, a conductive microneedle patch can be obtained.

[0081] Example 4

[0082] A microneedle patch, the preparation method of which is as follows:

[0083] S1 Preparation of hydrogel solution

[0084] Hydrogel solution III: 2 g of PEGDA was dissolved in 20 mL of deionized water to obtain a 10% PEGDA solution, and 12 mg of tartrazine and 20 mg of LAP photoinitiator were added to obtain hydrogel solution III, which was used for curing to prepare an antifouling layer.

[0085] Hydrogel solution II: 100 mg of reduced graphene oxide was added to 20 mL of deionized water to obtain a reduced graphene oxide aqueous dispersion with a dispersion concentration of 5 mg / mL. The solution was ultrasonically treated for 1 h to obtain a stable and uniform reduced graphene oxide / water dispersion, and then 4 g of ACG was added to 20 mL of the reduced graphene oxide aqueous dispersion, and 12 mg of lemon yellow and 20 mg of LAP photoinitiator were added to obtain hydrogel solution II, which was used for curing to prepare an adhesion layer.

[0086] Hydrogel solution I: 5 mg of EGCG and 200 mg of DexMA were dissolved in 1 mL of deionized water to form an EGCG / DexMA solution, 0.005 mg of bFGF was added to the EGCG / DexMA solution, and then 0.06 wt% mg of tartrazine and 0.1 wt% of LAP photoinitiator were added to obtain hydrogel solution I, which was used for curing to prepare a microneedle array.

[0087] S2 3D curing printing

[0088] The prepared hydrogel solution is added into the material tank in sequence. The printing order is anti-fouling layer, adhesion layer, and microneedle array. After each layer is printed, new solution is added into the material tank.

[0089] Curing conditions of the outer anti-fouling layer as the microneedle backing: light intensity 15mW / cm 2 , exposure time 15s, base layer exposure time 17s.

[0090] Curing conditions for the inner adhesive layer of the microneedle backing: light intensity 16mW / cm 2 , exposure time 16s, base layer exposure time 18s.

[0091] Curing conditions of microneedle array: light intensity 13mW / cm 2 , exposure time 16s, base layer exposure time 16s.

[0092] After printing, soak it in water for 5 minutes to remove the incompletely polymerized monomers. After drying and demoulding, a conductive microneedle patch can be obtained.

[0093] Example 5

[0094] A microneedle patch, the preparation method of which is as follows:

[0095] S1 Preparation of hydrogel solution

[0096] Hydrogel solution III: 2 g of PEGDA was dissolved in 20 mL of deionized water to obtain a 10% PEGDA solution, and 12 mg of tartrazine and 20 mg of LAP photoinitiator were added to obtain hydrogel solution III, which was used for curing to prepare an antifouling layer.

[0097] Hydrogel solution II: 100 mg of reduced graphene oxide was added to 20 mL of deionized water to obtain a reduced graphene oxide aqueous dispersion with a dispersion concentration of 5 mg / mL. The solution was ultrasonically treated for 1 h to obtain a stable and uniform reduced graphene oxide / water dispersion, and then 4 g of ACG was added to 20 mL of the reduced graphene oxide aqueous dispersion, and 12 mg of lemon yellow and 20 mg of LAP photoinitiator were added to obtain hydrogel solution II, which was used for curing to prepare an adhesion layer.

[0098] Hydrogel solution I: 10 mg of EGCG and 300 mg of DexMA were dissolved in 1 mL of deionized water to form an EGCG / DexMA solution, 0.001 mg of bFGF was added to the EGCG / DexMA solution, and then 0.06 wt% mg of tartrazine and 0.1 wt% of LAP photoinitiator were added to obtain hydrogel solution I, which was used for curing to prepare a microneedle array.

[0099] S2 3D curing printing

[0100] The prepared hydrogel solution is added into the material tank in sequence. The printing order is anti-fouling layer, adhesion layer, and microneedle array. After each layer is printed, new solution is added into the material tank.

[0101] Curing conditions of the outer anti-fouling layer as the microneedle backing: light intensity 15mW / cm 2 , exposure time 15s, base layer exposure time 17s.

[0102] Curing conditions for the inner adhesive layer of the microneedle backing: light intensity 16mW / cm 2 , exposure time 16s, base layer exposure time 18s.

[0103] Curing conditions of microneedle array: light intensity 13mW / cm 2 , exposure time 16s, base layer exposure time 16s.

[0104] After printing, soak it in water for 5 minutes to remove the incompletely polymerized monomers. After drying and demoulding, a conductive microneedle patch can be obtained.

[0105] Example 6

[0106] A microneedle patch, the preparation method of which is as follows:

[0107] S1 Preparation of hydrogel solution

[0108] Hydrogel solution III: 2 g of PEGDA was dissolved in 20 mL of deionized water to obtain a 10% PEGDA solution, and 12 mg of tartrazine and 20 mg of LAP photoinitiator were added to obtain hydrogel solution III, which was used for curing to prepare an antifouling layer.

[0109] Hydrogel solution II: 100 mg of reduced graphene oxide was added to 20 mL of deionized water to obtain a reduced graphene oxide aqueous dispersion with a dispersion concentration of 5 mg / mL. The solution was ultrasonically treated for 1 h to obtain a stable and uniform reduced graphene oxide / water dispersion, and then 4 g of ACG was added to 20 mL of the reduced graphene oxide aqueous dispersion, and 12 mg of lemon yellow and 20 mg of LAP photoinitiator were added to obtain hydrogel solution II, which was used for curing to prepare an adhesion layer.

[0110] Hydrogel solution I: 5 mg of EGCG and 300 mg of DexMA were dissolved in 1 mL of deionized water to form an EGCG / DexMA solution, 0.01 mg of bFGF was added to the EGCG / DexMA solution, and then 0.06 wt% mg of tartrazine and 0.1 wt% of LAP photoinitiator were added to obtain hydrogel solution I, which was used for curing to prepare a microneedle array.

[0111] S2 3D curing printing

[0112] The prepared hydrogel solution is added into the material tank in sequence. The printing order is anti-fouling layer, adhesion layer, and microneedle array. After each layer is printed, new solution is added into the material tank.

[0113] Curing conditions of the outer anti-fouling layer as the microneedle backing: light intensity 15mW / cm 2 , exposure time 15s, base layer exposure time 17s.

[0114] Curing conditions for the inner adhesive layer of the microneedle backing: light intensity 16mW / cm 2 , exposure time 16s, base layer exposure time 18s.

[0115] Curing conditions of microneedle array: light intensity 13mW / cm 2 , exposure time 16s, base layer exposure time 16s.

[0116] After printing, soak it in water for 5 minutes to remove the incompletely polymerized monomers. After drying and demoulding, a conductive microneedle patch can be obtained.

[0117] Comparative Example 1

[0118] A microneedle patch, the preparation method of which is as follows:

[0119] S1 Preparation of hydrogel solution

[0120] Hydrogel solution III: 2 g of PEGDA was dissolved in 20 mL of deionized water to obtain a 10% PEGDA solution, and 12 mg of tartrazine and 20 mg of LAP photoinitiator were added to obtain hydrogel solution III, which was used for curing to prepare an antifouling layer.

[0121] Hydrogel solution II: 100 mg of reduced graphene oxide was added to 20 mL of deionized water to obtain a reduced graphene oxide aqueous dispersion with a dispersion concentration of 5 mg / mL. The solution was ultrasonically treated for 1 h to obtain a stable and uniform reduced graphene oxide / water dispersion, and then 4 g of ACG was added to 20 mL of the reduced graphene oxide aqueous dispersion, and 12 mg of lemon yellow and 20 mg of LAP photoinitiator were added to obtain hydrogel solution II, which was used for curing to prepare an adhesion layer.

[0122] Hydrogel solution I: 10 mg of EGCG and 300 mg of DexMA were dissolved in 1 mL of deionized water to form an EGCG / DexMA solution, and then 0.06 wt% mg of tartrazine and 0.1 wt% of LAP photoinitiator were added to obtain hydrogel solution I, which was used for curing to prepare a microneedle array.

[0123] S2 3D curing printing

[0124] The prepared hydrogel solution is added into the material tank in sequence. The printing order is anti-fouling layer, adhesion layer, and microneedle array. After each layer is printed, new solution is added into the material tank.

[0125] Curing conditions of the outer anti-fouling layer as the microneedle backing: light intensity 15mW / cm 2 , exposure time 15s, base layer exposure time 17s.

[0126] Curing conditions for the inner adhesive layer of the microneedle backing: light intensity 16mW / cm 2 , exposure time 16s, base layer exposure time 18s.

[0127] Curing conditions of microneedle array: light intensity 13mW / cm 2 , exposure time 16s, base layer exposure time 16s.

[0128] After printing, soak it in water for 5 minutes to remove the incompletely polymerized monomers. After drying and demoulding, a conductive microneedle patch can be obtained.

[0129] Comparative Example 2

[0130] A microneedle patch, the preparation method of which is as follows:

[0131] S1 Preparation of hydrogel solution

[0132] Hydrogel solution III: 2 g of PEGDA was dissolved in 20 mL of deionized water to obtain a 10% PEGDA solution, and 12 mg of tartrazine and 20 mg of LAP photoinitiator were added to obtain hydrogel solution III, which was used for curing to prepare an antifouling layer.

[0133] Hydrogel solution II: 100 mg of reduced graphene oxide was added to 20 mL of deionized water to obtain a reduced graphene oxide aqueous dispersion with a dispersion concentration of 5 mg / mL. The solution was ultrasonically treated for 1 h to obtain a stable and uniform reduced graphene oxide / water dispersion, and then 4 g of ACG was added to 20 mL of the reduced graphene oxide aqueous dispersion, and 12 mg of lemon yellow and 20 mg of LAP photoinitiator were added to obtain hydrogel solution II, which was used for curing to prepare an adhesion layer.

[0134] Hydrogel solution I: 0.01 mg of bFGF and 300 mg of DexMA were dissolved in 1 mL of deionized water to form a bFGF / DexMA solution, and then 0.06 wt% mg of tartrazine and 0.1 wt% of LAP photoinitiator were added to obtain hydrogel solution I, which was used for curing to prepare a microneedle array.

[0135] S2 3D curing printing

[0136] The prepared hydrogel solution is added into the material tank in sequence. The printing order is anti-fouling layer, adhesion layer, and microneedle array. After each layer is printed, new solution is added into the material tank.

[0137] Curing conditions of the outer anti-fouling layer as the microneedle backing: light intensity 15mW / cm 2 , exposure time 15s, base layer exposure time 17s.

[0138] Curing conditions for the inner adhesive layer of the microneedle backing: light intensity 16mW / cm 2 , exposure time 16s, base layer exposure time 18s.

[0139] Curing conditions of microneedle array: light intensity 13mW / cm 2 , exposure time 16s, base layer exposure time 16s.

[0140] After printing, soak it in water for 5 minutes to remove the incompletely polymerized monomers. After drying and demoulding, a conductive microneedle patch can be obtained.

[0141] Comparative Example 3

[0142] A microneedle patch, the preparation method of which is as follows:

[0143] S1 Preparation of hydrogel solution

[0144] Hydrogel solution III: 2 g of PEGDA was dissolved in 20 mL of deionized water to obtain a 10% PEGDA solution, and 12 mg of tartrazine and 20 mg of LAP photoinitiator were added to obtain hydrogel solution III, which was used for curing to prepare an antifouling layer.

[0145] Hydrogel solution II: 4 g of ACG was added to 20 mL of deionized water, and 12 mg of tartrazine and 20 mg of LAP photoinitiator were added to obtain hydrogel solution II, which was used for curing to prepare an adhesion layer.

[0146] Hydrogel solution I: 10 mg of EGCG and 300 mg of DexMA were dissolved in 1 mL of deionized water to form an EGCG / DexMA solution, 0.01 mg of bFGF was added to the EGCG / DexMA solution, and then 0.6 mg of tartrazine and 1 mg of photoinitiator were added to obtain hydrogel solution I, which was used for curing to prepare a microneedle array.

[0147] S2 3D curing printing

[0148] The prepared hydrogel solution is added into the material tank in sequence. The printing order is anti-fouling layer, adhesion layer, and microneedle array. After each layer is printed, new solution is added into the material tank.

[0149] Curing conditions of the outer anti-fouling layer as the microneedle backing: light intensity 15mW / cm 2 , exposure time 15s, base layer exposure time 17s.

[0150] Curing conditions for the inner adhesive layer of the microneedle backing: light intensity 16mW / cm 2 , exposure time 16s, base layer exposure time 18s.

[0151] Curing conditions of microneedle array: light intensity 13mW / cm 2 , exposure time 16s, base layer exposure time 16s.

[0152] After printing, soak it in water for 5 minutes to remove the incompletely polymerized monomers. After drying and demoulding, a conductive microneedle patch can be obtained.

[0153] Comparative Example 4

[0154] A microneedle patch, the preparation method of which is as follows:

[0155] S1 Preparation of hydrogel solution

[0156] Hydrogel solution III: 2 g of PEGDA was dissolved in 20 mL of deionized water to obtain a 10% PEGDA solution, and 12 mg of tartrazine and 20 mg of LAP photoinitiator were added to obtain hydrogel solution III, which was used for curing to prepare an antifouling layer.

[0157] Hydrogel solution II: 100 mg of reduced graphene oxide was added to 20 mL of deionized water to obtain a reduced graphene oxide aqueous dispersion with a dispersion concentration of 5 mg / mL. The solution was ultrasonically treated for 1 h to obtain a stable and uniform reduced graphene oxide / water dispersion, and then 1 g of ACG was added to 20 mL of the reduced graphene oxide aqueous dispersion, and 12 mg of lemon yellow and 20 mg of LAP photoinitiator were added to obtain hydrogel solution II, which was used for curing to prepare an adhesion layer.

[0158] Hydrogel solution I: 10 mg of EGCG and 300 mg of DexMA were dissolved in 1 mL of deionized water to form an EGCG / DexMA solution, 0.01 mg of bFGF was added to the EGCG / DexMA solution, and then 0.6 mg of tartrazine and 1 mg of photoinitiator were added to obtain hydrogel solution I, which was used for curing to prepare a microneedle array.

[0159] S2 3D curing printing

[0160] The prepared hydrogel solution is added into the material tank in sequence. The printing order is anti-fouling layer, adhesion layer, and microneedle array. After each layer is printed, new solution is added into the material tank.

[0161] Curing conditions of the outer anti-fouling layer as the microneedle backing: light intensity 15mW / cm 2 , exposure time 15s, base layer exposure time 17s.

[0162] Curing conditions for the inner adhesive layer of the microneedle backing: light intensity 16mW / cm 2 , exposure time 16s, base layer exposure time 18s.

[0163] Curing conditions of microneedle array: light intensity 13mW / cm 2 , exposure time 16s, base layer exposure time 16s.

[0164] After printing, soak it in water for 5 minutes to remove the incompletely polymerized monomers. After drying and demoulding, a conductive microneedle patch can be obtained.

[0165] Comparative Example 5

[0166] A microneedle patch, the preparation method of which is as follows:

[0167] S1 Preparation of hydrogel solution

[0168] Hydrogel solution III: 2 g of PEGDA was dissolved in 20 mL of deionized water to obtain a 10% PEGDA solution, and 12 mg of tartrazine and 20 mg of LAP photoinitiator were added to obtain hydrogel solution III, which was used for curing to prepare an antifouling layer.

[0169] Hydrogel solution II: 100 mg of reduced graphene oxide was added to 20 mL of deionized water to obtain a reduced graphene oxide aqueous dispersion with a dispersion concentration of 5 mg / mL. The solution was ultrasonically treated for 1 h to obtain a stable and uniform reduced graphene oxide / water dispersion, and then 6 g of ACG was added to 20 mL of the reduced graphene oxide aqueous dispersion, and 12 mg of lemon yellow and 20 mg of LAP photoinitiator were added to obtain hydrogel solution II, which was used for curing to prepare an adhesion layer.

[0170] Hydrogel solution I: 10 mg of EGCG and 300 mg of DexMA were dissolved in 1 mL of deionized water to form an EGCG / DexMA solution, 0.01 mg of bFGF was added to the EGCG / DexMA solution, and then 0.6 mg of tartrazine and 1 mg of photoinitiator were added to obtain hydrogel solution I, which was used for curing to prepare a microneedle array.

[0171] S2 3D curing printing

[0172] The prepared hydrogel solution is added into the material tank in sequence. The printing order is anti-fouling layer, adhesion layer, and microneedle array. After each layer is printed, new solution is added into the material tank.

[0173] Curing conditions of the outer anti-fouling layer as the microneedle backing: light intensity 15mW / cm 2 , exposure time 15s, base layer exposure time 17s.

[0174] Curing conditions for the inner adhesive layer of the microneedle backing: light intensity 16mW / cm 2 , exposure time 16s, base layer exposure time 18s.

[0175] Curing conditions of microneedle array: light intensity 13mW / cm 2 , exposure time 16s, base layer exposure time 16s.

[0176] After printing, soak it in water for 5 minutes to remove the incompletely polymerized monomers. After drying and demoulding, a conductive microneedle patch can be obtained.

[0177] Performance Testing

[0178] The microneedle patches prepared in the examples and comparative examples were tested for performance, and the results are as follows.

[0179] 1. Appearance of microneedles

[0180] Figure 2 An image of a conductive microneedle patch obtained according to an embodiment of the present invention is shown.

[0181] 2. Single needle mechanical properties

[0182] Test method: Place the microneedle patch sample on the sample stage with the tip facing upward, and adjust the sample stage height so that both the upper and lower surfaces are in contact with the fixture. Compress at a constant rate of 0.05 mm / s, and record the compression displacement (L) and load (P) until the set displacement end point. The mechanical strength of a single needle is the ratio of the load to the number of needle tips.

[0183] The test results are shown in Table 3:

[0184] Table 3 Single needle mechanical strength test results of each embodiment and comparative example

[0185]

[0186]

[0187] Since myocardial tissue has a certain toughness and elasticity, penetrating myocardial tissue requires a certain mechanical strength of the microneedle. The test results in Table 3 show that the main factor affecting the tip strength is the mass concentration of DexMA in the tip. The higher the mass concentration, the higher the mechanical strength of the single needle. The addition of bFGF and EGCG has little effect on the mechanical strength of the tip.

[0188] 3. Conductivity test

[0189] Test method: The conductivity of the microneedle patches obtained in the embodiment and the comparative example was tested using a four-probe conductivity meter, and each test was repeated three times.

[0190] Table 4 Conductivity test of hydrogel microneedles

[0191]

[0192]

[0193] As can be seen from Table 4, the microneedle patch without the addition of reduced graphene oxide has a relatively low conductivity (Comparative Example 3). An appropriate amount of ACG helps to form a stable conductive network, helps rGO to form a continuous conductive path, and improves the conductive performance. ACG content that is too low or too high will affect the conductivity of the patch. This may be due to the presence of a small amount of oxygen-containing functional groups on the surface of the reduced graphene oxide, and the large π bonds on the surface, which improves electron transfer, resulting in the reduced graphene oxide itself having good conductivity; in addition, an appropriate amount of ACG can improve the dispersibility of rGO in the solution or matrix, prevent rGO sheets from agglomerating, thereby maintaining or slightly improving the conductive performance, but when the content is low, the dispersibility may not be enough. When the ACG content is too high, it may over-cover the surface of rGO, hinder the electron transfer channel between rGO sheets, increase the overall resistance of the material, and cause the conductive performance to decrease. In short, ACG and rGO affect each other, and their ratio is adjusted to adjust the conductivity of the material.

[0194] The electrical conductivity of the myocardium is usually between 0.1 and 0.6 S / m, which is sufficient to support the propagation of cardiac electrical activity, ensure that electrical signals can be effectively conducted, and coordinate the contraction of the heart. It can be seen that the electrical conductivity of the microneedle patch of Examples 1-6 of the present invention is similar to that of the myocardium, indicating that it has great potential for regulating the conduction of electrical signals in myocardial tissue.

[0195] 4. Antioxidant capacity test

[0196] Test method: The antioxidant performance of different embodiments and comparative examples was evaluated by scavenging 1,1-diphenyl-2-pyridylhydrazide (DPPH) free radicals. The mixture of different embodiments and comparative examples and DPPH reagent was stirred and incubated in the dark for 30 minutes, and the remaining DPPH was analyzed by UV-visible spectroscopy. The scavenging rate of DPPH was determined as follows:

[0197] DVC (%) = [(A blank - A positive control) / A blank] × 100%

[0198] D (%) = [[A blank - (A measurement - A control)] / A blank] × 100%

[0199] from Figure 3 It can be seen that the efficiency of scavenging free radicals increases with the increase of EGCG concentration, indicating that EGCG can effectively scavenge free radicals and has a good antioxidant effect. In addition, combined with Comparative Example 1, it can be seen that bFGF also has a certain effect on the antioxidant activity of EGCG, and can promote EGCG to exert its antioxidant effect to a certain extent, and has a certain synergistic effect with EGCG.

[0200] 5. Evaluation of anti-inflammatory effect in rats

[0201] According to the test results of 1-4, the microneedle patch of Example 2 was selected to conduct animal experiments to evaluate the application effect of the microneedle patch of the embodiment of the present invention.

[0202] Test method: Rats were anesthetized with 3% sodium pentobarbital (30 mg / kg) by intraperitoneal injection. The rats' chest and armpit hair were shaved with a small animal shaver (to fully expose the surgical area), and the surgical area was disinfected with iodine and 75% ethanol. Tracheal intubation: After anesthesia, MI surgery can be performed if there is no reaction to the toe clip test. Turn on the external light source, microscope switch, and ventilator, set the parameters (respiratory ratio 2:1, tidal volume 6-8mL, frequency 70 times / min), insert the tracheal intubation tube along the glottis, remove the rat and connect it to the ventilator, observe the rat's respiratory condition, and the chest rise and fall consistent with the ventilator frequency indicates that the intubation is successful, and MI surgery can be performed. The rat is placed in the right lateral decubitus position, and ophthalmic scissors are used under the left forelimb armpit, and microscissors are used to open the chest cavity between the third and fourth ribs to fully expose the heart. Microscopic straight forceps gently pick up a small amount of pericardium and tear a little pericardium under the left atrial appendage to fully expose the left anterior descending coronary artery (LAD) or the area where it is located. Ligation of coronary artery: Find the direction or possible location of LAD under a microscope, take 5-0 suture with needle in the needle holder, and pass the left anterior descending coronary artery (LAD) with 5-0 non-invasive suture next to the pulmonary artery cone below the root of the left atrial appendage to completely block the blood flow of LAD. Closure of chest: After ligation, attach the microneedle patch of Example 2 to the myocardial tissue at the infarction site, completely suture the chest opening with 5-0 suture (to ensure no gaps and no dislocation) to close the chest cavity, and suture each layer of muscle and skin layer by layer from the inside to the outside.

[0203] Heart tissue samples were collected 3 days after surgery, washed in pre-cooled PBS (0.02 mol / L, pH 7.0-7.2) to remove blood, and weighed for later use; 1.0 g of tissue block was transferred into a glass homogenizer, and 5 mL of pre-cooled PBS was added for thorough grinding. This process had to be performed on ice; the obtained homogenate was repeatedly frozen and thawed twice, and the prepared homogenate was centrifuged at 5000×g for 5 minutes, and the supernatant was retained for detection using an ELISA kit.

[0204] At the same time, a myocardial infarction model group and a sham operation group were set up for comparison. The comparison results were as follows Figure 4 shown.

[0205] from Figure 4 It can be seen that compared with the myocardial infarction model group, the microneedle patch loaded with EGCG and bFGF can effectively reduce the expression levels of inflammatory factors TNF-α, IL-6, and IL-β, providing a stable microenvironment for myocardial repair.

[0206] The technical features of the above-mentioned embodiments can be combined arbitrarily. To make the description concise, all possible combinations of the technical features in the above-mentioned embodiments are not described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification. It should be pointed out that for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be based on the attached claims.

Claims

1. A conductive hydrogel microneedle patch for myocardial repair, comprising a backing and a microneedle array, characterized in that: The microneedle array is solidified by a hydrogel solution I, wherein the hydrogel solution I contains methacryloyl dextran, epigallocatechin gallate, and basic fibroblast growth factor; The backing comprises an adhesive layer and an anti-fouling layer, wherein the adhesive layer is connected to the microneedle array, is located on the inner side of the backing, and is solidified from a hydrogel solution II, wherein the hydrogel solution II comprises methacrylylated glycine and reduced graphene oxide; The anti-fouling layer is located on the outside of the backing and is formed by curing the hydrogel solution III, wherein the hydrogel solution III includes polyethylene glycol diacrylate; The hydrogel solution I comprises 1 mg / mL-10 mg / mL of epigallocatechin gallate, 100 mg / mL-300 mg / mL of methacryloyl dextran, and 0.001 mg / mL-0.01 mg / mL of basic fibroblast growth factor; The hydrogel solution II contains, based on the amount of water, 20 wt% methacrylylated glycine and 5 mg / mL reduced graphene oxide.

2. The conductive hydrogel microneedle patch according to claim 1, characterized in that: The methacryloyl dextran is prepared by the following method: Dextran, dimethyl sulfoxide and 4-dimethylaminopyridine are mixed and stirred, glycidyl methacrylate is added, stirred, dialyzed and freeze-dried to obtain the methacrylylated dextran.

3. The conductive hydrogel microneedle patch according to claim 1, characterized in that: The reduced graphene oxide is prepared by mixing L-ascorbic acid and a graphene oxide aqueous solution under the conditions of pH=9 and 90°C.

4. The conductive hydrogel microneedle patch according to claim 3, characterized in that: The graphene oxide is prepared by adding concentrated sulfuric acid to graphite, stirring in a low-temperature ice bath, adding potassium permanganate in batches, stirring and reacting in a 37°C water bath after being fully mixed, and then stirring and reacting at 25°C; subsequently, slowly adding deionized water I to the reaction solution, heating the water bath to 90°C for reaction after the generated gas is released, and finally adding deionized water II to dilute the reaction solution, cooling the reaction solution to room temperature naturally after the reaction is terminated, adding 30% hydrogen peroxide solution until no bubbles are generated, and standing the reaction solution until it is cooled, reacting with 10% dilute hydrochloric acid and barium chloride solution, repeatedly centrifuging until no precipitation is generated, and continuously washing with deionized water until the reaction solution is neutral to obtain the graphene oxide.

5. The conductive hydrogel microneedle patch according to claim 1, characterized in that: In the hydrogel solution III, the content of polyethylene glycol diacrylate is 10 wt % based on the amount of water.

6. The conductive hydrogel microneedle patch according to claim 1, characterized in that: The polyethylene glycol diacrylate is prepared by the following method: Polyethylene glycol is dissolved in anhydrous toluene at 40° C. under a nitrogen environment, triethylamine is added after cooling to room temperature, acryloyl chloride is added dropwise after stirring evenly, and the reaction is stirred. Then the obtained polymer is precipitated in n-hexane. After the precipitate is purified, it is dissolved in water, dialyzed, and freeze-dried to obtain the polyethylene glycol diacrylate.

7. The method for preparing the conductive hydrogel microneedle patch according to any one of claims 1 to 6, characterized in that: The conductive hydrogel microneedle patch is prepared by 3D printing and curing, and the printing order is: anti-fouling layer, adhesion layer, microneedle array. After printing, the incompletely polymerized monomers are removed by water immersion, and the conductive hydrogel microneedle patch is obtained after drying and demoulding.

Citation Information

Patent Citations

  • A polymeric system for release of an active agent

    CN105120909A

  • Hydrogel, microneedle and preparation method and application thereof

    CN114805713A